Acute Kidney Injury after Major Abdominal Surgery: A Retrospective Cohort Analysis - Catarina Teixeira; Rosário Rosa; Natacha Rodrigues; Inês Mendes; Lígia Peixoto; Sofia Dias; Maria João Melo; Marta Pereira; Henrique Bicha Castelo; José António Lopes (Critical Care Research and Practice)
Background. We analyzed the incidence, risk factors, and prognosis of acute kidney injury (AKI) in a cohort of patients undergoing major abdominal surgery. Methods. A total of 450 patients were retrospectively studied. AKI was defined by an increase in serum creatinine (SCr) ≥ 0.3 mg/dl or by an increase in SCr ≥ 50% and/or by a decrease in urine output to 0.5 ml/kg/hour for 6 hours, in the first 48 hours after surgery. Logistic regression method was used to determine predictors of AKI and in-hospital mortality. A two-tailed P value <0.05 was considered significant. Results. One hundred one patients (22.4%) had postoperative AKI. Age (adjusted odds ratio (OR) 1.02, 95% confidence interval (CI) 1.01–1.05), nonrenal Revised Cardiac Risk Index score (adjusted OR 1.9, 95% CI 1.3–3.1, P=0.003), intraoperative erythrocytes transfusions (adjusted OR 2.2, 95% CI 1.4–3.5, P <.0001), and nonrenal Simplified Acute Physiology Score II (adjusted OR 1.03, 95% CI 1.01–1.06, P=0.0191) were associated with postoperative AKI. AKI was associated with increased in-hospital mortality (20.8% versus 2.3%, P <.0001; unadjusted OR 11.2, 95% CI 4.8–26.2, P <.0001; adjusted OR 3.7, 95% CI 1.2–11.7, P=0.024). Conclusion. AKI was common in patients undergoing major abdominal surgery and was associated with in-hospital mortality.